2017
DOI: 10.3892/mmr.2017.6710
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of hyperoside isolated from Zanthoxylum bungeanum leaves on SW620 human colorectal cancer cells via induction of the p53 signaling pathway and apoptosis

Abstract: The present study aimed to demonstrate the antiproliferative effect of hyperoside from Zanthoxylum bungeanum leaves (HZL) and explain the underlying molecular mechanisms in the SW620 human colorectal cancer cell line. The cytotoxic effects of HZL were determined using a3-(4,5-dimethylthiazol-2-yl)2,5-diphenyltetrazolium bromide assay. Apoptosis and cell cycle were detected using flow cytometry. Reactive oxygen species (ROS) levels and mitochondrial membrane potential (∆Ψm) were assessed using 2′,7′-dichloroflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…The biofunctions of hyperoside were mainly involved in antioxidants, hypoglycemic, anti-cancer, anti-inflammatory and cardiovascular effects [19]. Previous studies have showed that hyperoside can help with the amelioration of lung cancer [20], pancreatic cancer [21], prostate cancer [22] and colon cancer [23]. However, whether hyperoside has therapeutic effects on breast cancer remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The biofunctions of hyperoside were mainly involved in antioxidants, hypoglycemic, anti-cancer, anti-inflammatory and cardiovascular effects [19]. Previous studies have showed that hyperoside can help with the amelioration of lung cancer [20], pancreatic cancer [21], prostate cancer [22] and colon cancer [23]. However, whether hyperoside has therapeutic effects on breast cancer remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, according to the results of the structure–activity relationship of nine flavonoids from Z. bungeanum leaves (Zhang, Wang, Yang, Zhou, & Zhang, ) and the correlation between the chromatographic fingerprint and antioxidant activity of the 22 subsequent fractions of Z. bungeanum leaves ethanol extracts (Zhang, Luo, Wang, He, & Li, ; Zhang, Luo, & Wang, ), it was found that quercitrin, hyperoside, rutin, and afzelin were the dominant flavonoids, which played a major role in antioxidant and antimicrobial activity. Furthermore, hyperoside from Z. bungeanum leaves also exerts many bioactivities, such as antiproliferative effects against SW620 (Zhang, Dong, Zhang, & Zhang, ) and antihyperglycemic and hepatocyte‐protective effects (Zhang, Wang, Dong, Yu, & Zhang, ). Therefore, in view of these benefits, it is necessary to establish a simple, low‐cost and efficient purification method for the four flavonoids from Z. bungeanum leaves.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to discover that five classical signaling pathways play pivotal roles in the tumorigenesis of LUAD and can be targeted by known compounds. These five pathways, including pathways in cancer, and chemokine, MAPK, p53, and Fc epsilon RI signaling pathways, have been studied in multiple cancers, including LUAD . After analyzing these five pathways in CMap, several known compounds were identified.…”
Section: Discussionmentioning
confidence: 99%